سلطة القاضي الدستوري في الرقابة على الإنحراف التشريعي - علي طه (جامعة النجاح الوطنية, 2025)
This thesis examines the authority of the constitutional judge in overseeing legislative deviation. It aims to analyze the concept of legislative deviation, its various forms, and the tools employed by constitutional judges to detect and address such deviations. The study adopts a comparative analytical approach by analyzing constitutional texts and judicial rulings across multiple countries, supplemented by relevant jurisprudential studies. The primary objective of this research is to assess the effectiveness of judicial oversight in confronting legislative deviation and to propose recommendations that could enhance the role of constitutional courts in safeguarding the constitution. The study is grounded in a central research question: to what extent does the constitutional judge possess the authority to confront legislative deviations, and how can the effectiveness of this oversight be strengthened to ensure the stability of constitutional and legal systems, while protecting fundamental rights and freedoms? The research concludes with several key findings and recommendations. Chief among them is the necessity of ensuring effective oversight over legislative deviation as a means to protect the constitution and guarantee public rights and freedoms. It also emphasizes the importance of developing oversight mechanisms in line with evolving political dynamics within societies. Moreover, the thesis stresses the importance of maintaining the independence of the constitutional judiciary and preventing any interference by other branches of power, in order to ensure judicial impartiality and safeguard individual and societal rights.
The Authority of Constitutional Judges to Oversee Legislative Deviations